The experiences and perceptions of genitally mutilated females and healthcare practitioners in South Eastern Nigeria - Obiora, Oluchukwu Loveth (My University, 2020)
Background: Female Genital Mutilation (FGM), also referred to as Female Genital Cutting (FGC) or female circumcision (FC), remains a contributor to the high morbidity and mortality among females in Africa. Despite concerted efforts to curb it, the practice continues among many ethnic groups, especially in Africa. Various studies have been conducted, focusing on this practice. However, in Africa, there is a paucity of literary work on the experiences of females who underwent FGM/C, and the experiences of healthcare practitioners who care for these genitally mutilated females is also unknown. Aim of the study: The aim of this study was to obtain insight into the Female Genital Mutilation/ cutting (FGM/C) experiences of females and healthcare practitioners in South Eastern (SE), Nigeria where the United Nations Children’s Fund (UNICEF) and the United Nations Population Fund (UNFPA) Nigeria (2016) reported a steady rise in their FGM/C prevalence; and also to develop a comprehensive, context-specific health education pamphlet (HEP) for the females based on the identified health information needs. The study was underpinned by the self-concept theory and the theory of ethical relativism. Methods: This was a multi-method study which employed a scoping literature review, a qualitative descriptive method, and a methodological triangulation for the development of a HEP for the genitally mutilated females. Therefore, the study had three phases. Phase one was the scoping literature review of FGM/C in Africa, Phase two was a qualitative description of the FGM/C experiences of genitally mutilated females, mothers of genitally mutilated girls and the healthcare practitioners in SE Nigeria, while Phase three was the development of a health education pamphlet (HEP) for use by the genitally mutilated females. Findings: The first phase of the study revealed FGM/C was still being practiced widely in Africa despite interventions such as anti-FGM/C laws and campaigns. Evidence found has also revealed there might have been an increase in “early-age” (0 to 10 years) FGM/C in some communities, and that the FGM/C studies done between 1 January 2007 and 31 December 2016 were mostly quantitative studies focused on the prevalence, attitude, perpetrators and health consequences of FGM/C. Studies investigating the experiences of all the role players involved in this practice and how to prevent it were absent. Understanding these phenomena could guide efforts to curb this harmful practice. In the second phase of the study, the participants equated FGM/C to male circumcision and noted that culture was mostly responsible for the continuation of the practice over the years. Regardless of the pain associated with this practice, some of the participants were forcefully circumcised to ensure adherence to their culture. Among the female participants, feelings of uncertainty, fear, and helplessness were experienced. Moreover, healthcare practitioners reported feelings of not being adequately equipped with the advanced skills required in the care of genitally mutilated females, especially during childbirth. Also reported were cases of child mortality and other healthcare challenges owing to FGM/C. In the third phase, three synthesized findings were generated from the methodological triangulation of conclusions from Phases one and two: “FGM/C: past and present situations,” “factors that sustained FGM/C” and “health information needs.” In response to the health information needs identified, a health education pamphlet (HEP) was developed to improve self-care among the females. Conclusion: This study provided evidence that FGM/C is ongoing in Africa. Although it is illegal in many countries, females and healthcare practitioners still support this procedure as it is seen as a part of the culture. Some women were forcefully circumcised. Feelings of uncertainty, fear and helplessness were reported among the females. Cases of child mortality and other healthcare challenges due to FGM/C were also experienced. In response to the information needs that emerged from the scoping review and the qualitative investigation, a health education pamphlet was developed to inform the genitally mutilated females on what FGM/C was all about, self-care after FGM/C, and what to do when under pressure to circumcise their daughters
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy, 2020